DISEÑO DE UN PORTAFOLIO EDITORIAL CON LINEAS GRÁFICAS PARA PUBLICACIONES CIENTIFICAS - Quinzo Porras, Amanda Belén (2019)
At present, this branch has become demanding, an attractive layout must be followed, but its concept and functionality must always be preserved, with the support of new styles and trends that continue to evolve to facilitate readability, composition and aesthetics diagramming of scientific articles, granting of compositional, typographic, chromatic parameters, to correctly implement the different processes for the production of printed and digital books and scientific journals. For the execution of an article, it is necessary to have a printed guide with the parameters that serve for the development of the same, in order to contribute with the personal and professional development for the people dedicated to the layout of the articles, it was proposed to develop the investigation. To achieve this, the editorial portfolio is made up of two parts: the first presents a brief description of the elements of a journal, its possible variations and an example of its current application in the publications of scientific dissemination of the medium. The second brief description of the fundamental aspects of editorial design in these publications. To obtain reliable results, you can opt for a field and descriptive investigation with a quantitative approach that allows you to achieve the desired results for the development of the proposal, which must meet the needs of the reader.